Metal‐Free Synthesis of β‐Bromoalkenyl Sulfides via Deoxygenative Bromination/Olefination/Sulfenylation of Ketones with Sulfonyl Hydrazides and Pyridinium Tribromide. Issue 11 (19th September 2018) - Bao, Yishu; Zhong, Lingyu; Hou, Qiaodan; Zhou, Qingfa; Yang, Fulai
Abstract: A novel metal‐free method for synthesis of β‐bromoalkenyl sulfides via deoxygenative bromination/olefination/sulfenylation process using commercially available ketones, sulfonyl hydrazides and pyridinium tribromide as starting materials has been developed. In this reaction, pyridinium tribromide plays the role of oxidant and substrate, wherein water and molecular nitrogen are generated as environmentally benign by‐products. Preliminary investigation revealed that vinyl bromides were critical intermediate. Importantly, this protocol not only obviates the use of alkynes and traditional sulfenylating agents, but also reveals that ketones can be used as precursors of vinyl bromides. Abstract : A novel metal‐free method for synthesis of β‐bromoalkenyl sulfides via deoxygenative bromination/olefination/sulfenylation process using commercially available ketones, sulfonyl hydrazides and pyridinium tribromide as starting materials has been developed.